The voice as felt sense: an integrative review exploring the potential of embodied voice work in trauma-informed dramatherapy - Rodin, Danieyella (My University, 2023)
This integrative research paper draws from diverse disciplines like neuroscience, trauma studies, therapeutic voicework and theatre voice studies to interrogate the relevance and applicability of embodied voice work in trauma-informed drama therapy. Through a neurophenomenological approach to these topics, the distinction between traumatic cognition and neurobiological experience is explored as primarily an embodied experience. This is supported by findings that voice work sits at the crossroads between cognitive and bodybased therapeutic approaches and is applicable in both, as the voice has the potential to holistically express the felt sense of any moment. Additionally, since voicelessness and silence are so often a part of the traumatic event, giving clients an opportunity to speak vitally redresses these past wounds. Given their theatre voice training background, drama therapists are uniquely placed to work with and develop the spoken voice. And the spoken voice is a tool which, I argue, should be given more attention, particularly within trauma-informed therapeutic frameworks.
A research report submitted to the School of Arts, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of requirements for the degree of Master of Arts by coursework and research report in the field of Drama Therapy, 2023
Keywords: Neuroscience; Therapeutic voicework; Theatre voice studies